Implementation of an Ask Me 3 ® education video to improve outcomes in post-myocardial infarction patients - Amy Marie Winiger; Katherine Shue-McGuffin; Ashley Moore-Gibbs; Kathleen Jordan; Anita Blanchard (Elsevier, 2021)
Objective: The Advanced Practice Providers (APPs) in an adult cardiology practice in a large metropolitan city, provide hospital follow-up care to post-myocardial infarction (MI) patients. The APPs identified a problem: patients retained very little of the information they receive during their hospitalization. The purpose of this pilot project was to evaluate the impact of an Ask Me 3 ® post-MI education video on patients' knowledge of self-care activities. The video was designed to promote secondary prevention of cardiovascular disease and support optimal cardiovascular health.Methods: The project used a pre-test post-test quasi-experimental design to evaluate the feasibility and efficacy of a post-MI education video compared to the standard teaching methods.Results: The sample consisted of 25 total participants, 12 in the control group and 13 in the intervention group. The increase in the intervention group's post- test scores was statistically significant (p value = 0.0056), showing a vast improvement in knowledge with the addition of an "Ask Me 3" education video.Conclusion: An "Ask Me 3" post-MI education video may effectively improve cardiovascular secondary prevention when incorporated with the standard teaching methods. Patients may view the video multiple times, enhancing their knowledge of lifestyle modifications following hospitalization and their overall cardiovascular health.